-5-(m+8)+6m=4(m+2)

Simple and best practice solution for -5-(m+8)+6m=4(m+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-(m+8)+6m=4(m+2) equation:


Simplifying
-5 + -1(m + 8) + 6m = 4(m + 2)

Reorder the terms:
-5 + -1(8 + m) + 6m = 4(m + 2)
-5 + (8 * -1 + m * -1) + 6m = 4(m + 2)
-5 + (-8 + -1m) + 6m = 4(m + 2)

Combine like terms: -5 + -8 = -13
-13 + -1m + 6m = 4(m + 2)

Combine like terms: -1m + 6m = 5m
-13 + 5m = 4(m + 2)

Reorder the terms:
-13 + 5m = 4(2 + m)
-13 + 5m = (2 * 4 + m * 4)
-13 + 5m = (8 + 4m)

Solving
-13 + 5m = 8 + 4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-4m' to each side of the equation.
-13 + 5m + -4m = 8 + 4m + -4m

Combine like terms: 5m + -4m = 1m
-13 + 1m = 8 + 4m + -4m

Combine like terms: 4m + -4m = 0
-13 + 1m = 8 + 0
-13 + 1m = 8

Add '13' to each side of the equation.
-13 + 13 + 1m = 8 + 13

Combine like terms: -13 + 13 = 0
0 + 1m = 8 + 13
1m = 8 + 13

Combine like terms: 8 + 13 = 21
1m = 21

Divide each side by '1'.
m = 21

Simplifying
m = 21

See similar equations:

| 2(2x-1)-27= | | -2(3t-4)+4t=2t-5 | | 140=-7(1+7p) | | 3m+2(m+2)=13-(2m-5) | | 3m+2(m+2)=13-(2m-5) | | 14x+35=315 | | X*0.6666666666666667=34 | | 49+-1x=129+-9x | | -3+6x-x=42 | | 4+3x=4(4x+6) | | -4(v+4)=9v-3 | | 6x+7(x+1)=20 | | t=5.3(4)+9.5 | | -2+.66x=8 | | 49+-1x=129 | | 3x+2(3x+11)=112 | | 13.7b-3=3-4b | | 2.65=3(1+x)+x | | 3+7p-4=p+6p-1 | | 7x+8=7(x-8) | | -4+3k=12+k | | -222=6(7a-2) | | 8n-16=24+3n | | 3+7p-4+p=6p-1 | | 1y=-5x+b | | -2.3y=-4.5 | | 11(-8)=x | | 190=x+.07x | | (x^2-3)(3x^2+4x-1)= | | .33x-9=11 | | 5x-6y=-19 | | 1x-41=3 |

Equations solver categories